A FORM OF SOCIAL AND RELIGIOUS INCLUSION: THE DEAF MINISTRY IN BRAZIL (Social and Environmental Law Journal, 2024)
The inclusion of deaf individuals in the everyday actions of religious life is one of the significant challenges for religious communities in Brazil. The objective of this work is to analyze the process of inclusion (or exclusion) of deaf individuals in the Catholic Church, focusing on the activities of the Deaf Ministry in Brazil. We question whether participation in the activities of the Deaf Ministry helps deaf individuals feel more socially included, thereby reinforcing their dignity. The methodology used involved an online survey with semi-structured interviews conducted in 2022, alongside a bibliographic research of published studies on the topic. We followed four stages in this investigation: religion, exclusion, inclusion, and the Deaf Ministry. The concepts were discussed based on contributions from Otto Marques da Silva, Romeu Kazumi, Maria Teresa Eglér Mantoan, César Augusto de Assis Silva, Luiz Carlos Dutra, Karin Lillian Strobel, Serge Paugam, Simon Schwartzman, as well as inclusive legislation that is a reference on this topic. To better understand the reality experienced by deaf individuals, an empirical study was conducted through a questionnaire containing 12 open and closed questions. The questionnaire was distributed to three groups: agents of the Deaf Ministry, deaf individuals attending the Deaf Ministry in Brazil, and Catholic religious leaders responsible for activities that include deaf individuals. Field research was carried out across the 19 regional offices of the Deaf Ministry of the Catholic Church in Brazil, with 162 interviews conducted.
Keywords: Exclusion; Inclusion; Deaf Ministry; Religion